Molybdopterin biosynthesis pathway contributes to the regulation of SaeRS two-component system by ClpP in Staphylococcus aureus. Issue 1 (31st December 2022) - Zhao, Na; Wang, Yanan; Liu, Junlan; Yang, Ziyu; Jian, Ying; Wang, Hua; Ahmed, Mahmoud; Li, Min; Bae, Taeok; Liu, Qian
ABSTRACT: In Staphylococcus aureus, the SaeRS two-component system is essential for the bacterium's hemolytic activity and virulence. The Newman strain of S. aureus contains a variant of SaeS sensor kinase, SaeS L18P. Previously, we showed that, in the strain Newman, SaeS L18P is degraded by the membrane-bound protease FtsH. Intriguingly, the knockout mutation of clpP, encoding the cytoplasmic protease ClpP, greatly reduces the expression of SaeS L18P. Here, we report that, in the strain Newman, the positive regulatory role of ClpP on the SaeS L18P expression is due to its destabilizing effect on FtsH and degradation of MoeA, a molybdopterin biosynthesis protein. Although the transcription of ftsH was not affected by ClpP, the expression level of FtsH was increased in the clpP mutant. The destabilizing effect appears to be indirect because ClpXP did not directly degrade FtsH in an in vitro assay. Through transposon mutagenesis, we found out that the moeA gene, encoding the molybdopterin biosynthesis protein A, suppresses the hemolytic activity of S. aureus along with the transcription and expression of SaeS L18P. In a proteolysis assay, ClpXP directly degraded MoeA, demonstrating that MoeA is a substrate of the protease. In a murine bloodstream infection model, the moeA mutant displayed reduced virulence and lower survival compared with the WT strain. Based on these results, we concluded that ClpP positively controls the expression of SaeS L18P in an FtsH and MoeA-dependent manner, and the physiological role of MoeA outweighs its suppressive effect on the SaeRS TCS during infection.